MBOs performance of state owned enterprises: the case of China - Xu Feng (2018)
By reviewing and analyzing the MBO cases of 66 Chinese listed companies in the last ten years, this study draws the MBO map of Chinese enterprises and finds that the main problems in the MBOs of Chinese enterprises are the unreasonable pricing of MBOs and the lack of incentive mechanisms at the management level. In this study, 19 state-owned enterprises that are listed companies were selected as samples and the corresponding industry pairing enterprises were also selected. 2793 sample firm financial data items of 19 firms were obtained by calculating 21 financial performance indicators 7 years before and after acquisition. The financial performance indicators of this study were analyzed through DuPont financial analysis, analysis of cash flow index, analysis of scale index, analysis of investment index and change of financial performance. The financial data was analyzed through regression analysis. The analysis found that the MBOs of Chinese state-owned enterprises were better developed than the industry in terms of profitability, operational ability, debt paying ability, cash flow and asset scale. In terms of cash flow, the growth rate of net cash flow after MBO improved. In terms of asset size, the company’s annual asset growth rate was positive after deducting industry factors before and after MBO. This indicates that the scale of assets of the sample enterprises was increasing when compared with the industry. However, the regression analysis, after controlling the sample selection bias and factors such as the company's asset management, showed that the financial indicators of the company have not significantly improved after the MBO, suggesting that the MBOs of state-owned enterprises in China exhibited a relatively low efficiency.